(untitled) (Praxis Educativa, 2026)
We developed an 18-month master’s thesis proposal seminar with an “authentic production-based teaching approach” to shorten the distance between teaching and learning academic writing. Over the course of 10 years, the seminar has been redefined to preserve the nature of the literacy practices it seeks to teach, while considering the educational needs of its students. Our analysis details the seminar design to help participants effectively produce their thesis proposals and construct the knowledge required to elaborate it, driven by the need to solve the problems their production entails. This paper examines the instructional decisions regarding time frames, work cycles, tasks, guidelines, assignments, use of written models and bibliographic material, and student and teacher roles.